Tanggung Jawab Sosial, Ekonomi, dan Ekologis dalam Perspektif Teologi Pastoral: Refleksi atas Bencana di Indonesia dalam Terang Gaudium et Spes 63–72 - Rosalia Enny Astuti; Sutami, Florensius; Wyatno, Anthony Kuniawan; Anang, Noverin Andrea; Simanjuntak, Helmina; Hartanto, Sukiahwati; Pailing, Yulius Roge (Sekolah Tinggi Teologi Kadesi Bogor, 2026)
Indonesia is a disaster-prone region where calamities are frequently exacerbated by the spiritual crisis of modern humanity, manifested as individualism and a dominant technocratic paradigm,This article explores social, economic, and ecological responsibilities in light of the Pastoral Constitution Gaudium et Spes (GS) articles 63–72 and the encyclical Laudato Si’ (LS) as a response to the reality of disasters in Indonesia,The research employs a qualitative approach using a descriptive-analytical method based on library research Findings indicate that GS 63–72 positions human dignity at the center of economic life, where the principle of the